2008
DOI: 10.1186/gb-2008-9-7-r115
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gene expression in drug resistant Leishmania is associated with gene amplification, gene deletion and chromosome aneuploidy

Abstract: Background: Drug resistance can be complex, and several mutations responsible for it can coexist in a resistant cell. Transcriptional profiling is ideally suited for studying complex resistance genotypes and has the potential to lead to novel discoveries. We generated full genome 70-mer oligonucleotide microarrays for all protein coding genes of the human protozoan parasites Leishmania major and Leishmania infantum. These arrays were used to monitor gene expression in methotrexate resistant parasites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
208
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(220 citation statements)
references
References 89 publications
(101 reference statements)
7
208
0
4
Order By: Relevance
“…A copy of the targeted gene was always present as a result of chromosome duplications (tri-or tetrasomy), wholegenome duplication, or translocation of the chromosome fragment carrying the target gene. Aneuploidy was also observed in laboratory strains of L. major and L. infantum after induction of drug resistance: transcriptional profiling using microarrays identified altered expression of genes on six different chromosomes in both species [10,11]. Quantitative Southern blot and comparative genomic hybridizations confirmed that the variation in expression corresponded to changes in the copy number of these chromosomes.…”
Section: The Flexible Genomes Of Leishmaniamentioning
confidence: 84%
See 1 more Smart Citation
“…A copy of the targeted gene was always present as a result of chromosome duplications (tri-or tetrasomy), wholegenome duplication, or translocation of the chromosome fragment carrying the target gene. Aneuploidy was also observed in laboratory strains of L. major and L. infantum after induction of drug resistance: transcriptional profiling using microarrays identified altered expression of genes on six different chromosomes in both species [10,11]. Quantitative Southern blot and comparative genomic hybridizations confirmed that the variation in expression corresponded to changes in the copy number of these chromosomes.…”
Section: The Flexible Genomes Of Leishmaniamentioning
confidence: 84%
“…By contrast, chromosome gain or loss (aneuploidy) in multicellular eukaryotes is either lethal or results in severe abnormalities, for example trisomy of chromosome 21 in humans with Down syndrome [6]. Despite the predominantly negative effects of aneuploidy, supernumerary chromosomes have been reported in tumor cells, yeast, and recently the protozoan Leishmania [7][8][9][10][11].…”
Section: The Flexible Genomes Of Leishmaniamentioning
confidence: 99%
“…3A). Reduced RNA levels in Leishmania are usually due to a decrease in gene copy number (61,62), although other mechanisms may also occur (63). Interestingly, in the yeast S. cerevisiae that also transports AdoMet, resistance to SNF was shown to correlate with loss of function mutations in the AdoMet transporter Sam3 (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although methotrexate (MTX) is not used against Leishmania, it is nonetheless very active and has been extensively studied. Leishmania cells selected for MTX resistance undergo amplification of the dihydrofolate reductasethymidylate synthase (DHFR-TS) and pteridine reductase 1 (PTR1) genes, which encode primary (30,31) and secondary targets of MTX (32,33), respectively. Because of this unique combination of drug target relationship with MTX, we first validated Cos-Seq with parasites selected under MTX pressure.…”
Section: Significancementioning
confidence: 99%
“…A recent study has highlighted the role of protein phosphatase 2A in the mode of MTX action in mammalian cells (34). Thus, considering that MTX has similar mechanisms of action and entails comparable resistance mechanisms in Leishmania and mammalian cells (30,31,35), the two phosphatase-related genes emerged as reasonable candidates. Indeed, on the transfection of LinJ.34.2310 and LinJ.…”
Section: Significancementioning
confidence: 99%